ANALYSIS OF SERVICE QUALITY, PRICE, AND BRAND IMAGE ON GOJEK CUSTOMERS SATISFACTION IN BALI - Ribek P.K.; Agung A.P.; Kharisnawati G.; Yuliastuti I.A.N. (Russian Journal of Agricultural and Socio-Economic Sciences)
Digitalization is one of the most important things used to increase sales in various businesses. This study aims to determine the effect of service quality on customer satisfaction, the effect of price on customer satisfaction, and brand image on customer satisfaction. The research method is quantitative, with a population of all Gojek users who have used the service at least five times. The research sample was 170 respondents. This study uses SPSS multiple linear regression analysis. 26. The results of the study state that the analysis of service quality, price, and brand image has a positive and significant effect on customer satisfaction. This study found that Gojek provides the best quality in satisfying customers by being responsive, friendly, and protecting customers.